2019
DOI: 10.15381/rivep.v30i1.15700
|View full text |Cite
|
Sign up to set email alerts
|

Sucesión bacteriana del tracto digestivo del lechón alimentado con ensilado biológico

Abstract: Se evaluó mediante análisis metagenómico la composición y abundancia de la microbiota bacteriana en tres porciones del tracto gastrointestinal de un lechón, en el alimento balanceado y en ensilados biológicos preparados con residuos de origen acuícola. Se extrajo el ADN de las muestras y se procedió con la secuenciación. La mayor diversidad bacteriana estuvo en el alimento balanceado (44.7%), predominando Candidatus phytoplasma surgarcane. En el ensilado biológico predominaron las especies Lactobacillus casei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Khafipour et al (2016) concluded that the increased ratio of Firmicutes to Bacteroidetes resulting from a high concentration diet is an undesirable outcome that interferes with the degradation and digestion of dietary fiber. What is more, bio-concentrates have also been found in other animals to cause changes in the gastrointestinal microbe (Súarez et al 2019). The present study showed that the addition of bio-concentrate to mixed silage and sorghum silage-based diets resulted in an increase in Firmicutes and a decrease in Bacteroidetes, indicating the ability of bioconcentrate to optimize rumen bacterial microbiota.…”
Section: Discussionsupporting
confidence: 57%
“…Khafipour et al (2016) concluded that the increased ratio of Firmicutes to Bacteroidetes resulting from a high concentration diet is an undesirable outcome that interferes with the degradation and digestion of dietary fiber. What is more, bio-concentrates have also been found in other animals to cause changes in the gastrointestinal microbe (Súarez et al 2019). The present study showed that the addition of bio-concentrate to mixed silage and sorghum silage-based diets resulted in an increase in Firmicutes and a decrease in Bacteroidetes, indicating the ability of bioconcentrate to optimize rumen bacterial microbiota.…”
Section: Discussionsupporting
confidence: 57%